ANALISIS PENENTUAN LUAS PRODUKSI PADA PERUSAHAAN ROTI BANGKIT JAYA DI KOTA KUPANG - Raimundus Ivan Naisoko; Christien C Foenay; Antonio E L Nyoko (Universitas Kristen Wira Wacana Sumba, 2021)
The purpose of this study is to analyze the determination of production volumeto maximize profits. This research is a quantitative research. Data analysis techniques are Forecasting and Linear Programming (Simplex Method). The result of analysis concluded thatthe production volume using Linear Programming simplex method obtained in 2019 should produce as many as 405,792,000 molten chocolate bread per year and by 2020 should produce as many as 4,107,480 molten chocolate bread per year for earning maximum profit. Meanwhile, the Forecasting result is to produce 4 types of bread as many as 6,308,240 breads in 2019 and 6,365,560 breads in 2020. In terms of profit optimization then calculation using Linear Programming is better however considering the marketing aspect where consumers require a variety of bread flavors then calculation using forecasting method is more recommended.